String-based flapping mechanism and modularized trailing edge control system for insect-type FWMAV. (April 2019) - Gong, DuHyun; Lee, DaWoon; Shin, SangJoon; Kim, SangYong
This paper presents the design process and experimental results of a brand new flapping and trailing edge control mechanism for a flapping wing micro air vehicle. The flapping mechanism, whose main components are fabricated from string, is suggested and optimized further by a modified pattern search method. The trailing edge control mechanisms for pitching and rolling moments are designed to be attached onto the present flapping mechanism in a modularized fashion. Prototypes of both mechanisms are fabricated and experimentally tested in order to examine the feasibility of the designs. It is expected that the present flapping mechanism will generate enough lift for the total weight of the vehicle. The present control mechanism is found to be able to supply sufficient control moment.